Prototheca Infections and Ecology from a One Health Perspective - Libisch, Balázs; Picot, Carine; Ceballos-Garzon, Andrés; Moravkova, Monika; Klimesová, Marcela; Telkes, Gábor; Chuang, Shih-Te; Le Pape, Patrice (Microorganisms, 2022)
Prototheca microalgae were only recognized as pathogens of both humans and animals in the 1960s; however, since then, these microbes have been drawing increasing interest in both human and veterinary medicine. The first human outbreak of protothecosis in a tertiary care chemotherapy ward in 2018 further highlighted the need to understand in more depth and detail their ecology, etiology, pathogenesis and routes of transmission between different hosts, environments and habitats from a One Health perspective. Protothecal infections have been reported in a growing number of cattle herds around the world in recent decades, and Prototheca has become an important bovine mastitis pathogen in certain countries and regions. The survival of Prototheca in the environment and its ability to spread in the herd pose a serious challenge to the management of infected dairy farms. Prevention of the disease is particularly important, as there is no effective and reliable treatment for it and the chances of self-healing are minimal. Therefore, the development of more effective drugs is needed for the treatment of human and animal protothecosis. The prudent use of antibiotics and their replacement by alternative or preventive measures, when possible, may further contribute to the control of protothecal infections.
Keywords: food safety; ecology; protothecosis; One Health; Prototheca; mastitis